Caveolin-1: an ambiguous entity in breast cancer - Naveen Chintalaramulu; Dhirendra Pratap Singh; Biplov Sapkota; Dayanidhi Raman; Suresh Alahari; Joseph Francis (Molecular Cancer)
Abstract Breast cancer (BC) is the most frequently diagnosed cancer in women and the second leading cause of death from cancer among women. Metastasis is the major cause of BC-associated mortality. Accumulating evidence implicates Caveolin-1 (Cav-1), a structural protein of plasma membrane caveolae, in BC metastasis. Cav-1 exhibits a dual role, as both a tumor suppressor and promoter depending on the cellular context and BC subtype. This review highlights the role of Cav-1 in modulating glycolytic metabolism, tumor-stromal interactions, apoptosis, and senescence. Additionally, stromal Cav-1's expression is identified as a potential prognostic marker, offering insights into its contrasting roles in tumor suppression and progression. Furthermore, Cav-1's context-dependent effects are explored in BC subtypes including hormone receptor-positive, HER2-positive, and triple-negative BC (TNBC). The review further delves into the role of Cav-1 in regulating the metastatic cascade including extracellular matrix interactions, cell migration and invasion, and premetastatic niche formation. The later sections discuss the therapeutic targeting of Cav-1 by metabolic inhibitors such as betulinic acid and Cav-1 modulating compounds. While Cav-1 may be a potential biomarker and therapeutic target, its heterogeneous expression and context-specific activity necessitates further research to develop precise interventions. Future studies investigating the mechanistic role of Cav-1 in metastasis may pave the way for effective treatment of metastatic BC.